2017
DOI: 10.1111/ctr.13121
|View full text |Cite
|
Sign up to set email alerts
|

The role of complement‐fixing donor‐specific antibodies identified by a C1q assay after heart transplantation

Abstract: Routine monitoring of DSA post-transplant, and their characterization using the C1q assay, may provide prognostic information for acute rejection after heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…We found the presence of preformed IgG+ DSA at transplant to be associated with pAMR development, as has been reported by others; however, we also observed that 86% of patients who developed pAMR2 had new C1q+ DSA at the time of diagnosis, supporting the hypothesis that complement fixation plays an important role in the pathology of pAMR . It is possible that the lower incidence of AMR in this study is the result of our institutional policy to ensure a C1q‐DSA‐negative VXM at the time of donor acceptance, although further study is warranted.…”
Section: Discussionsupporting
confidence: 89%
“…We found the presence of preformed IgG+ DSA at transplant to be associated with pAMR development, as has been reported by others; however, we also observed that 86% of patients who developed pAMR2 had new C1q+ DSA at the time of diagnosis, supporting the hypothesis that complement fixation plays an important role in the pathology of pAMR . It is possible that the lower incidence of AMR in this study is the result of our institutional policy to ensure a C1q‐DSA‐negative VXM at the time of donor acceptance, although further study is warranted.…”
Section: Discussionsupporting
confidence: 89%
“…The reason for this significant difference in age is unclear, with similar findings in other studies relating to both heart and kidney transplantation. 23 , 24 The frequency of antibodies targeting HLA class II antigens compared to HLA class I was statistically significant ( P =.005), a phenomenon which was previously reported by other investigators. 16 , 22 The literature also shows a higher proportion of antibodies targeting the HLA-DQ and DR antigens, 16 , 22 which was also demonstrated during our analysis, particularly with regards to HLA-DQ.…”
Section: Discussionsupporting
confidence: 80%
“…A multitude of factors contribute to accelerated allograft rejection in allosensitized recipients, such as acute complement fixation by preformed DSAs 40‐42 and rapid memory cell recall responses 43‐46 . In the present investigation, we employed a sensitized mouse model of islet transplantation to (1) investigate underlying antidonor immune responses driving islet allograft rejection in sensitized recipients and (2) devise a donor apoptotic cell–based combination regimen that promotes long‐term allograft survival in these recipients.…”
Section: Discussionmentioning
confidence: 99%